Pengaruh Aplikasi Edukatif Islami di Era Digital terhadap Pengetahuan Agama Anak Usia Dini: Studi di TK Islam Terpadu, Kota Serang, Banten - Mustahidin, Arip Arizal; Lesiani, Lesi; Kangiden, Farida Ariyani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Islamic educational applications are one of the innovations that can make the teaching and learning process easier. Technological advancements, many educational institutions have begun to utilize Islamic educational applications as additional learning media. This app is designed to introduce the basic concepts of Islam through a fun and easy-to-understand method for children. However, although these applications promise benefits in increasing children's religious knowledge, there are a number of issues that need to be considered. This study aims to examine the influence of Islamic educational applications in the digital era on early childhood religious knowledge, especially in Integrated Islamic Kindergarten in Serang City, Banten. This study uses a quantitative approach with experimental design and data analysis using Smart PLS 3. The research population is early childhood in Integrated Islamic Kindergarten in Serang City, Banten. The results of this study show that Islamic educational applications in the digital era have a significant influence on the improvement of early childhood religious knowledge, especially in Integrated Islamic Kindergarten, Serang City, Banten. The use of this application not only enriches the religious learning process in a more interactive and interesting way, but also shows the effectiveness of technology in supporting religious education among children. This research also highlights the importance of the role of parents in accompanying children during the use of the application, as well as the need for quality application development both in terms of content and technology